2022
DOI: 10.1200/jco.21.02321
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib in Combination With Rituximab for Indolent Clinical Forms of Mantle Cell Lymphoma (IMCL-2015): A Multicenter, Open-Label, Single-Arm, Phase II Trial

Abstract: PURPOSE The need for an individualized management of indolent clinical forms in mantle cell lymphoma (MCL) is increasingly recognized. We hypothesized that a tailored treatment with ibrutinib in combination with rituximab (IR) could obtain significant responses in these patients. METHODS This is a multicenter single-arm, open-label, phase II study with a two-stage design conducted in 12 Spanish GELTAMO sites (ClinicalTrials.gov identifier: NCT02682641 ). Previously untreated MCL patients with indolent clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 25 publications
(79 reference statements)
0
28
0
Order By: Relevance
“…Ibrutinib with rituximab in indolent MCL (n = 50) was investigated. 112 After 36 months follow-up and after 12 cycles, the overall response rate (ORR) was 84% with 80% CR. Among the patients, 87% were MRD negative and at 2 years, 24 patients discontinued ibrutinib with undetectable MRD.…”
Section: Prognostic Factorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Ibrutinib with rituximab in indolent MCL (n = 50) was investigated. 112 After 36 months follow-up and after 12 cycles, the overall response rate (ORR) was 84% with 80% CR. Among the patients, 87% were MRD negative and at 2 years, 24 patients discontinued ibrutinib with undetectable MRD.…”
Section: Prognostic Factorsmentioning
confidence: 98%
“…Although not a standard practice, we sometimes refer the patients for leukapheresis to control lymphocytosis when the absolute lymphocyte count is >50 000 and then administer consolidation treatment. Ibrutinib with rituximab in indolent MCL ( n = 50) was investigated 112 . After 36 months follow‐up and after 12 cycles, the overall response rate (ORR) was 84% with 80% CR.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data from phase 2 studies indicated that ibrutinib plus rituximab-induced durable and high response and prolonged survival in patients with TN [ 170 ], R/R [ 169 , 237 ], and indolent [ 171 ] MCL. The CR rate (44–80%) and PFS (3-year survival 87%) were significantly elevated than that reported with single-agent ibrutinib, although the head-to-head comparison is not available [ 167 , 235 ].…”
Section: Btk Inhibitors In Hematological Malignanciesmentioning
confidence: 99%
“…The CR rate (44–80%) and PFS (3-year survival 87%) were significantly elevated than that reported with single-agent ibrutinib, although the head-to-head comparison is not available [ 167 , 235 ]. This combination regime also yielded 87% cases of uMRD in the peripheral blood of indolent MCL patients, contributing to the discontinuation of ibrutinib [ 171 ]. It should be noted that the efficacy of this combination may be reduced in the context of TP53-mutation and Ki-67 high expression [ 171 , 237 ].…”
Section: Btk Inhibitors In Hematological Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation